ANALISIS KONTRIBUSI KEPADATAN KENDARAAN BERMOTOR TERHADAP KONSENTRASI KARBON MONOKSIDA (CO) DAN TINGKAT KEBISINGAN DI JALAN SLAMET RIYADI SURAKARTA - Titis Anggitan; Husin Bugis; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
In the current era, the transportation is growing rapidly. It has an impact such as air and noise pollution. Carbon monoxide is one of the dangerous pollutants. While the noise comes from the sound of the vehicle engine, horn, and exhaust. Slamet Riyadi street Surakarta is a protocol road that has a high level of vehicle density. So it is necessary to conduct research with the aim of knowing the effect of motor vehicle density on carbon monoxide concentrations and noise levels. The results showed that the concentration of Carbon monoxide on Slamet Riyadi street Surakarta in the morning and evening exceeded the quality standard of 16038.26 µg/Nm3and 16141.58 µg/Nm3. During the day it is still below the quality standard, which is 9425.86 µg/Nm3. Meanwhile, the daytime noise level on Slamet Riyadi street Surakarta which is calculated by the Leq formula also exceeds the quality standard of 82.33 dBA.